Metal-free synthesis of nanocrystalline graphene on insulating substrates by carbon dioxide-assisted chemical vapor deposition. (February 2017) - Weber, Nils-Eike; Binder, Axel; Kettner, Michel; Hirth, Sabine; Weitz, R. Thomas; Tomović, Željko
Abstract: The scalable, low-cost fabrication of high quality graphene is a subject of intense research. Here, a novel method to synthesize uniform and large area graphene films directly on various high-temperature resistant insulating substrates such as SiO2 /Si, Al2 O3 and quartz glass by low pressure chemical vapor deposition (LP-CVD) using a mild oxidant (CO2 ) and a carbon source (CH4 ), without the aid of any metallic species or catalysts, is reported. The resulting films are uniform and homogeneous on a large scale and comprise nanocrystalline graphene domains. Raman spectroscopy, UV–Vis spectroscopy, X-ray photoelectron spectroscopy, atomic force microscopy and electrical transport measurements were used for an initial characterization of the synthesized graphene films. The optical and electrical properties of the film can be easily tuned together with layer thickness by controlling process conditions, like temperature, chamber pressure and process gas composition. The obtained graphene films show excellent electrical transport properties with high charge carrier mobilities up to 720 cm 2 /(Vs). These directly grown graphene films are readily applicable in a wide range of application fields, such as sensors, transparent conductive coatings and electronic devices. Graphical abstract: